2020
DOI: 10.1002/jmrs.403
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effect of tube potential on clinical image quality using direct digital detectors for pelvis and lumbar spine radiographs

Abstract: Introduction: High kVp techniques, 15% or 10-kVp rules, are well-known dose reduction methods. Traditionally, the use of high tube potential (i.e. increased kVp) is associated with decreased radiographic contrast and overall image quality. Recent studies suggest contrast and image quality are not heavily reliant on kVp with digital systems. This study aims to assess the effects of the high tube potential technique on clinical radiographic image quality when using digital systems, to validate high kVp as a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 18 publications
0
15
0
2
Order By: Relevance
“…Our study is very much set around clinical changes made within our department and as such we fully accept a large number of limitations with it, which we sought to list in the article. 1 Our study follows a previous basic pilot study that aimed to investigate image acquisition protocols established for film-screen technology as they now relate to digital radiography. 2 Following this study, our results suggested that there did not appear to exist an overwhelming difference in image contrast between exposures utilising a difference of 15% in kVp.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Our study is very much set around clinical changes made within our department and as such we fully accept a large number of limitations with it, which we sought to list in the article. 1 Our study follows a previous basic pilot study that aimed to investigate image acquisition protocols established for film-screen technology as they now relate to digital radiography. 2 Following this study, our results suggested that there did not appear to exist an overwhelming difference in image contrast between exposures utilising a difference of 15% in kVp.…”
mentioning
confidence: 99%
“…We did exclude a small number of images that would lead to such aberrations, an example of which Alzyoud et.al reference from our article as figure 1B. 1 Alzyoud et.al also raise interest in the variation of the VGA results that exist across the different images in the study and concern at the variation, and however, we are not necessarily surprised by the variation given the varied patient presentations we see within our department, which we have stipulated is a limitation of this retrospective study. This limitation was described in the article, in that we had no control over image acquisition conditions and patient size.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We read with interest a recent submission to the Journal of Medical Radiation Sciences entitled ‘An evaluation of the effect of tube potential on clinical image quality using direct digital detectors for pelvis and lumbar spine radiographs’ by Peacock, Steward and Riley 1 . We would like to thank the authors for their valuable contribution and acknowledge that they have attempted to assess an important issue and to provide further validation of high tube potential as a dose‐saving technique.…”
mentioning
confidence: 99%